2000
DOI: 10.1002/(sici)1526-4998(200005)56:5<455::aid-ps152>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biodegradation of a phenylurea herbicide, diuron?:?structure and toxicity of metabolites

Abstract: Microbial degradation, organic synthesis and ecotoxicology were used to investigate the fate of diuron after spreading on soils. Quantitative biodegradation assays were performed with fungal strains, showing that diuron was degraded but not entirely mineralized. The modifications observed consisted in demethylation of the terminal nitrogen atom. The identified metabolites were synthesized in sufficient amounts to confirm their structures and determine their non‐target toxicity using four biotests. The two meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 28 publications
(34 reference statements)
6
80
3
2
Order By: Relevance
“…Furthermore, the results for diuron and its degradation products indicated that most of the metabolites presented higher nontarget toxicity than the parent molecule. Among all the products tested, 3,4-DCA and the formylated derivative had the most toxic effects, thus corroborate previous studies (Tixier et al, 2000(Tixier et al, , 2001. This toxicity shows the potential risks involved in releasing molecules, which are transformed into the environment.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the results for diuron and its degradation products indicated that most of the metabolites presented higher nontarget toxicity than the parent molecule. Among all the products tested, 3,4-DCA and the formylated derivative had the most toxic effects, thus corroborate previous studies (Tixier et al, 2000(Tixier et al, , 2001. This toxicity shows the potential risks involved in releasing molecules, which are transformed into the environment.…”
Section: Discussionsupporting
confidence: 89%
“…A toxic effect of this metabolite is also reported in V. fischeri (Microtox test) with a 15 min-EC 50 of 1.1 mg/L, while a genotoxic effect was demonstrated with a dark mutant of V. fischeri (via the Mutatox test) by Osano et al (2002). Tixier et al (2000Tixier et al ( , 2001 showed a toxicity of diuron and 3,4-DCA on both V. fischeri and T. pyriformis and also demonstrated toxicity for the other metabolites D1, D2, D3, DCPMU, and DCPU. Globally, most of the metabolites presented a higher toxicity than diuron even if the assessment was related to the microbiotests used.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…With effect from December 2003, the European Union Drinking Water Directive (Council Directive 98/83/EC) has set limits of 0.03 µg/L for certain pesticides. Under the Directive there is currently no requirement for water supply organisations to measure pesticide metabolites despite evidence that their toxicity can be higher than the parent compound (Tixier et al, 2000;Tixier et al, 2001). There is a clear need therefore, to better understand the movement and transport of pesticides and their degradation products in both the thin soil zone, where most retardation and degradation is likely to take place, and in the aquifer itself.…”
Section: Introductionmentioning
confidence: 99%